A comprehensive assessment of the association between anemia, clinical covariates and outcomes in a population-wide heart failure registry. (15th May 2016) - Jonsson, Asa; Hallberg, Ann-Charlotte; Edner, Magnus; Lund, Lars H.; Dahlstrom, Ulf
Abstract: Background: The aim was to investigate the prevalence of, predictors of, and association with mortality and morbidity of anemia in a large unselected cohort of patients with heart failure (HF) and reduced ejection fraction (HFrEF) and to explore if there were specific subgroups of high risk. Methods: In patients with HFrEF in the Swedish Heart Failure Registry, we assessed hemoglobin levels and associations between baseline characteristics and anemia with logistic regression. Using propensity scores for anemia, we assessed the association between anemia and outcomes with Cox regression, and performed interaction and sub-group analyses. Results: There were 24 511 patients with HFrEF (8303 with anemia). Most important independent predictors of anemia were higher age, male gender and renal dysfunction. One-year survival was 75% with anemia vs. 81% without (p < 0.001). In the matched cohort after propensity score the hazard ratio associated with anemia was for all-cause death 1.34 (1.28-1.40; p < 0.0001), CV mortality 1.28 (1.20–1.36; p < 0.0001), and combined CV mortality or HF hospitalization 1.24 (1.18–1.30; p < 0.0001). In interaction analyses, anemia was associated with greater risk with lower age, male gender, EF 30-39%, and NYHA-class I-II. Conclusion: In HFrEF, anemia is associated with higher age, male gender and renal dysfunction and increased risk of mortality and morbidity. The influence of anemia on mortality was significantly greater in younger patients, in men, and in those with more stable HF. The clinical implication of these findings might be in the future to perform targeted treatment studies.